2006
DOI: 10.1143/jjap.45.l393
|View full text |Cite
|
Sign up to set email alerts
|

Deoxidization of Cu Oxide under Extremely Low Oxygen Pressure Ambient

Abstract: Cu oxide has been deoxidized in an extremely low oxygen partial pressure atmosphere. The oxygen was evacuated to 10-28 atm using a newly developed oxygen reduction system (ORS). It was experimentally demonstrated that the surface oxide of Cu film was completely removed by exposure to such an environment at 200 °C. The proposed deoxidization reaction can be used as a new Cu surface cleaning technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…It is a closed loop system and nitrogen gas circulates in it. The oxygen pump filters out oxygen impurity from nitrogen and creates extremely low p(O 2 ) [1]. The oxygen pump is basically a yttriastabilized zirconia (YSZ) tube equipped with platinum electrodes on its inner and outer walls (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a closed loop system and nitrogen gas circulates in it. The oxygen pump filters out oxygen impurity from nitrogen and creates extremely low p(O 2 ) [1]. The oxygen pump is basically a yttriastabilized zirconia (YSZ) tube equipped with platinum electrodes on its inner and outer walls (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…If one uses a readilyavailable nitrogen gas typically containing 1 ppm oxygen impurity, one still needs temperatures near 800 °C. If one can reduce p(O 2 ) down to 10 −27 atm, a spontaneous decomposition of CuO below 180 °C is expected [1].…”
Section: N Shirakawamentioning
confidence: 99%
“…8) Another approach is photonic sintering, where short, intense light pulses shone on the sample are mostly absorbed by the darker ink layer coated on the more reflective substrate, inducing thermal decomposition of the oxide. 9,10) Our approach to oxide reduction is to introduce oxygen pump technology, which we have been developing to create gases with an oxygen partial pressure p(O 2 ) as low as 10 À32 atm when measured at 600 C. 11) In such an extremely low p(O 2 ) environment, copper oxides decompose spontaneously into metal and oxygen when heated to moderate temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Dry reduction of Cu 2 O and/or CuO to Cu has been performed by hot filament hydrogen radical source [4], deoxidation process in the low oxygen pressure ambient [5], and low-pressure NH 3 [6] and H 2 plasmas [3,6] with the electron density in the range of ~10 12 cm -3 [7]. Sawada et al used He-H 2 atmospheric-pressure dielectric-barrier discharge (DBD) plasma to reduce Cu 2 O [8,9] and reported that the reduction speed was 10 nm/min while heating the substrate at 100°C.…”
Section: Introductionmentioning
confidence: 99%